Altered Sensory Insular Connectivity in Chronic Postsurgical Pain Patients - Ching, Yin Ying; Wang, Chenhao; Tay, Terence; Loke, Yng Miin; Tang, Phua Hwee; Sng, Ban Leong; Zhou, Juan (Frontiers in Human Neuroscience, 2018)
Abstract Chronic postsurgical pain (CPSP) occurs in up to 50% of individuals after surgeries and 32% after hysterectomy, leading to major adverse effects on quality of life and socioeconomic burden. Little is known about whether and how large-scale neural networks being affected in CPSP, particularly with regard to the functional connectivity (FC) of insula which is known to be the hub of the intrinsic neural network playing a critical role in pain processing. Here, we sought to examine the dynamics of insular FC in the context of noxious stimuli in CPSP patients. To this aim, task-free fMRI data were acquired, before and after acute heat pain stimulation, from 11 individuals with chronic post-hysterectomy pain (CPHP) and 22 age-matched healthy controls (HC) who had a hysterectomy but without chronic post-surgical pain. We examined whole-brain FC were mapped by seeding at the sensorimotor and chemosensory subfields of the insula and found significant group x stimulation interaction effects. Specifically, the HC group had increased FC between the left sensorimotor insula and right angular and middle occipital gyrus and increased FC between the left chemosensory insula and bilateral angular and middle occipital gyrus following pain stimulation. In contrast, such pain stimulation related FC changes were absent in the CPHP group. Furthermore, higher insular FC at baseline and smaller increased insular FC after pain stimulation correlated with clinical pain scores in CPHP patients. Our findings suggest that chronic postsurgical pain is associated with altered dynamics of large-scale functional networks anchored in the insula.